2018
DOI: 10.1093/ntr/nty073
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Engagement and Outcomes in the SmokefreeTXT Program: A Growth Mixture Modeling Analysis

Abstract: The current study enabled us to investigate differing engagement patterns in non-incentivized program participants, which can help inform program modifications in real-world settings. Lack of engagement and dropout continue to impede the potential effectiveness of mHealth interventions, and understanding patterns and predictors of engagement can enhance the impact of these programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 16 publications
5
33
0
Order By: Relevance
“…Our findings add to the mixed results seen in prior trials conducted in health care settings of SMS text messaging interventions for smoking cessation [32,58-61]. Our results also extend those of prior observational studies of SmokefreeTXT [62,63] and a related NCI SMS text messaging program designed specifically for veterans [64] demonstrating the challenges of sustaining end-user engagement in this program. End of treatment CO-defined brief smoking abstinence rates in our study were comparable with self-reported abstinence rates in these large-scale, noncontrolled, observational studies [62-64] but were notably lower than self-reported abstinence rates in an emergency department-based pilot study of a multicomponent smoking cessation program that included SmokefreeTXT [65].…”
Section: Discussionsupporting
confidence: 76%
“…Our findings add to the mixed results seen in prior trials conducted in health care settings of SMS text messaging interventions for smoking cessation [32,58-61]. Our results also extend those of prior observational studies of SmokefreeTXT [62,63] and a related NCI SMS text messaging program designed specifically for veterans [64] demonstrating the challenges of sustaining end-user engagement in this program. End of treatment CO-defined brief smoking abstinence rates in our study were comparable with self-reported abstinence rates in these large-scale, noncontrolled, observational studies [62-64] but were notably lower than self-reported abstinence rates in an emergency department-based pilot study of a multicomponent smoking cessation program that included SmokefreeTXT [65].…”
Section: Discussionsupporting
confidence: 76%
“…Consistent with previous studies [37,41], in this study, daily smoking was a risk factor for poor response and abstinence rates. Longer prequit time was associated with a lower likelihood of dropping out but a lower likelihood of abstinence at quit day.…”
Section: Discussionsupporting
confidence: 91%
“…The need to improve user retention, interaction with SmokefreeMOM until intervention end, and abstinence rates points to engagement as a coveted strategy [41,42]. Engagement strategies could involve incorporating additional keywords the user can text to interact with the intervention or providing congratulatory messages for interaction [43].…”
Section: Discussionmentioning
confidence: 99%
“…8 However, although mHealth strategies show potential, maintaining engagement is difficult and user drop-out rates are high when applied in real-world circumstances. 9,10 Thus, there is a need to understand how text-message programmes interact with patient characteristics and clinical factors to result in smoking cessation to optimise future programmes.…”
mentioning
confidence: 99%
“…There is some research which have identified lower smoking quantity, older age, male sex, higher education, and absence of depression as being associated with higher engagement with mHealth programmes, 10,15 and engagement with mHealth programmes has been associated with quitting smoking. 10,16,17 Research on text-message-based smoking cessation programmes has largely focused on assessing efficacy, 7 rather than assessing predictors of efficacy such as certain patient characteristics. The messages themselves guide the participants through the quitting process by providing tips and advice, as well as referring to other sources external to the message programme.…”
mentioning
confidence: 99%